2016
DOI: 10.1021/acs.macromol.5b02407
|View full text |Cite
|
Sign up to set email alerts
|

Photo-Cross-Linkable Polymeric Optoelectronics Based on the [2 + 2] Cycloaddition Reaction of Cinnamic Acid

Abstract: We report the synthesis of cinnamic acid-functionalized conjugated polymers, which are cross-linked via [2 + 2] cycloaddition by UV illumination, reducing their solubility. The cross-linking reaction was investigated by a combination of FTIR and optical spectroscopy, and an optimum condition for the solubility modulation of thin films, a major challenge in the solution-phase fabrication of layered optoelectronic devices, was reached. As proof of concept, OLEDs were fabricated, using these conjugated polymers a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…Not only it can form dicarboxylic acid monomer through [2 + 2] cycloaddition reaction first and then be applied for polyester synthesis (thermoplastic material), 17,18 but also it can be connected to the polymer side chain first and then through [2 + 2] cycloaddition reaction to form cross-linked network structure (thermosetting material). 19,20 Chung et al achieved crack healing in polymeric materials by photochemical [2 + 2] cycloaddition reaction of a cinnamate monomer, and the photochemical healing process was very fast without any catalyst or severe heat treatment. 21 Akashi et al synthesized the novel polylactides with both CA derivatives terminals showed higher thermal stabilities after UV irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…Not only it can form dicarboxylic acid monomer through [2 + 2] cycloaddition reaction first and then be applied for polyester synthesis (thermoplastic material), 17,18 but also it can be connected to the polymer side chain first and then through [2 + 2] cycloaddition reaction to form cross-linked network structure (thermosetting material). 19,20 Chung et al achieved crack healing in polymeric materials by photochemical [2 + 2] cycloaddition reaction of a cinnamate monomer, and the photochemical healing process was very fast without any catalyst or severe heat treatment. 21 Akashi et al synthesized the novel polylactides with both CA derivatives terminals showed higher thermal stabilities after UV irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, cross-linking is a more (atom-)economical approach. One prominent example is the dimerization of cinnamic esters 18 induced by UV irradiation. The radiation dose employed is crucial, as adverse photochemical processes can occur upon overexposure, which compromise device performance.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In contrast, cross-linking is a more (atom-)­economical approach. One prominent example is the dimerization of cinnamic esters induced by UV irradiation. The radiation dose employed is crucial, as adverse photochemical processes can occur upon overexposure, which compromise device performance. , Other protocols involve additives, i.e., diiodooctane as a cross-linking reagent for amines, nitrenes generated in situ by UV irradiation, , or (photo)­acids inducing cationic ring-opening polymerization (CROP) of oxetanes .…”
Section: Introductionmentioning
confidence: 99%
“…This usually requires additional photoresist materials and extra steps such as photoresist deposition, etching, and lift-off . Driven by the increasing demand of cost-efficient, scalable manufacturing of electronic devices, directly photopatternable electronic materials comprising patterning and optoelectronic functions have attracted considerable attention. , Researchers have developed a variety of strategies to realize photoinduced changes in the solubilities of organic optoelectronic materials, such as photochemical cross-linking, photochemical cleavage of solubilizing pendants, ,, photoisomerization, photoacid irradiation, photoinduced changes in doping, , and photoinduced backbone cleavage . Our group has developed negative-tone photoresist conjugated polymers that combine polythiophene or polythiophene- alt -benzothiadiazole backbones with photocleavable solubilizing pendants that eliminate from the backbone upon illumination. , In these materials, polymer in the unirradiated areas dissolves in organic solvents, while in the irradiated areas, where photolysis of the solubilizing side chains occurs, polymer remains.…”
Section: Introductionmentioning
confidence: 99%